Knowledge about COVID-19 among Citizens in Thi-Qar Governorate/Iraq: an Online Survey - Fatima J. Shinjar1 .; Ali T. Hameed2, Hussein A. Dabis1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Epidemics of infectious disease, such as coronavirus disease 2019 (COVID-19), necessitates knowledgeassessment of pertinent populations as fast as possible because the findings are of great importance to thepublic health response. This study aims to (i) Assess the knowledge of Iraqi residents about COVID-19 and(ii) Identify the relationship between certain demographic features and the overall knowledge. This studywas conducted in Thi-Qar governorate/Iraq, the researcher used an electronic survey questionnaire (usinggoogle form), the Uniform Resource Locator was distributed through social media platforms with briefintroduction concerning the study. The tool of the study (questionnaire) involved of two parts: demographics(4 items) and knowledge questionnaire (3 sub-domains including 12 items). The total correct answers ratewas (88.1%). Lowest answers rate scored in routes of transmission sub-domain (82.5%) while control andprevention (92.7%) sub-domain scored the highest rate. Mean knowledge score of 10.57 (standard deviation:1.5, Range: 0-12). Also, results display highly significant relationships between overall knowledge anddemographic characteristics (P <0.001).Conclusion: Most well-educated Iraqi residents, particularly males, are knowledgeable about COVID-19.However, this result should be generalized with caution due to limited sample representativeness.